Yield and water productivity of Bt cotton (Gossypium hirsutum) as influenced by temperature under semi-arid conditions of north-western India: field and simulation study - BUTTAR, G S; JALOTA, S K; SOOD, ANIL; BHUSHAN, BHARAT (The Indian Journal of Agricultural Sciences, 2012)
Cotton cultivation in semi-arid region of Indian Punjab is considered as most risky crop as its yield is very sensitive to weather parameters like rain and temperature. In future due to global warming increase in the temperature is expected, which is most likely to influence the growth and yield of this fiber crop like other cereal crops. Studies on the effect of temperature on the growth and seed yield of Bt cotton in this region are lacking. The present 2-year field and 15-year simulation studies concern to simulate the effect of temperature on duration of pheno-phases and seed yield of Bt cotton hybrid RCH 134 and also on crop water productivity. Simulations were run for 15 years (1991–2005) using the already customized CropSyst model. The simulated results indicated that with increase in temperature from 28 to 32oC, cotton seed yield was reduced to half (from 4 700 to 2 300 kg/ha) following a linear relation with high coefficient of determination (0.97), and the reduction was more with increased temperature during sowing to flowering stage than other pheno-phases. Total evapo-transpiration (ET) during crop period and crop water productivity was also decreased with increased temperature. Relationship of cotton seed yield was linear with ET and quadratic with total water supply (rain +irrigation). Real crop water productivity (yield/ET) and apparent crop water productivity (yield/irrigation water) were 0.362+0.129 and 0.485+0.120 kg/m3, respectively.